Flame-retardant synergist, low-smoke oil-resistant flame-retardant polyolefin cable material, preparation method of low-smoke oil-resistant flame-retardant polyolefin cable material and cable prepared from low-smoke oil-resistant flame-retardant polyolefin cable material
By using double hydroxide coated expandable graphite and silicone coated expandable graphite as flame retardant synergists in polyolefin cable materials, combined with other materials, the lack of aging resistance, oil resistance and flame retardant properties of traditional cable materials are solved. The problem of this problem achieves efficient mechanical strength and processing performance, and is suitable for high temperature and oil environments.
Patent Information
- Application Number
- CN202411372328.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional polyolefin cable materials have shortcomings in aging resistance, oil resistance and flame retardant properties, and cannot meet the performance requirements of modern power transmission.
Use double hydroxide-coated expandable graphite and silicone resin-coated expandable graphite as flame retardant synergists, combining high-density polyethylene, POE, hydrogenated nitrile rubber, nano-silica and metal hydroxide materials, Low smoke, oil-resistant flame retardant polyolefin cable materials are prepared by intricate refining and irradiation crosslinking processes.
It significantly improves the aging resistance, oil resistance and flame retardant properties of the cable, reduces the amount of flame retardant, achieves excellent mechanical strength and processing performance, and is suitable for high temperature and oil environments.
Smart Images

Figure BDA0005067905440000141 
Figure BDA0005067905440000151
Abstract
Description
Technical Field
[0001] The invention relates to the field of electric wires and cables, and in particular to a flame retardant synergist, a low-smoke, oil-resistant and flame-retardant polyolefin cable material, a preparation method and a cable made from the polyolefin cable material. Background Art
[0002] With the rapid development of industry and economy, power transmission plays a vital role as the infrastructure of modern society. In many industries, especially in petrochemical, mining and shipbuilding, cable oil resistance and flame retardancy are directly related to the stable operation of equipment and production lines. Traditional polyolefin cables are gradually unable to meet the various performance requirements of modern power transmission. Therefore, the development of a new type of polyolefin cable material with excellent aging resistance, oil resistance and flame retardancy has become the focus of technological innovation. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a flame retardant synergist, a low-smoke, oil-resistant and flame-retardant polyolefin cable material, a preparation method and a cable made from the polyolefin cable material, aiming to solve the problems of poor aging resistance, oil resistance and flame retardancy of traditional polyolefin cable materials.
[0004] To achieve the above-mentioned purpose, the present invention provides a flame retardant synergist, a low-smoke and oil-resistant flame retardant polyolefin cable material, a preparation method and a cable made from the polyolefin cable material. A flame retardant synergist, the ingredients of the flame retardant synergist include at least one of double hydroxide coated expandable graphite and silicone resin coated expandable graphite.
[0005] Optionally, the weight ratio of the double hydroxide coated expandable graphite to the silicone coated expandable graphite is (0-15): (0-15).
[0006] A low-smoke, oil-resistant and flame-retardant polyolefin cable material. The ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material, measured by weight, include: 20-30 parts of high-density polyethylene, 20-35 parts of POE, 15-25 parts of hydrogenated nitrile rubber, 5-10 parts of a compatibilizer, 25-45 parts of a flame retardant and 10-15 parts of a flame retardant synergist.
[0007] Optionally, the mass percentage of acrylonitrile in the hydrogenated nitrile rubber is 43%.
[0008] Optionally, the compatibilizer includes at least one of POE grafted maleic anhydride, PE grafted maleic anhydride, EVA grafted maleic anhydride and EMA grafted maleic anhydride.
[0009] Optionally, the flame retardant is a compound of nano-silicon dioxide and metal hydroxide, and the weight ratio of the nano-silicon dioxide to the metal hydroxide is (10-18): (15-27).
[0010] Optionally, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of a coupling agent, and the coupling agent is a silane coupling agent, which is at least one of vinyl triethoxy silane, vinyl trimethoxy silane, and vinyl tri (β-methoxyethoxy) silane.
[0011] Optionally, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of lubricant, and the lubricant is at least one of stearic acid, calcium stearate, magnesium stearate, polyethylene wax, paraffin and silicone.
[0012] Optionally, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of an antioxidant, and the antioxidant is at least one of dioctylamine, tri[2,4-di-tert-butylphenyl]phosphite, antioxidant PTLTP, and antioxidant AO-80.
[0013] Optionally, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 2-4 parts of a cross-linking aid, and the cross-linking aid is at least one of trimethylolpropane triacrylate (TMPTMA), ditrimethylolpropane tetraacrylate (DTMPTA), ethylene glycol diacrylate (EGDA) and ethylene glycol dimethacrylate (EGDMA).
[0014] To achieve the above object, the present invention also provides a method for preparing a low-smoke, oil-resistant and flame-retardant polyolefin cable material, comprising the following steps:
[0015] Preparation of flame retardant synergist: reacting a metal salt solution, sodium hydroxide and expandable graphite by a solution method and then centrifugally drying to obtain the double hydroxide coated expandable graphite; adding expandable graphite to a silicone resin organic solution, and curing the solution solution to obtain the silicone resin coated expandable graphite, wherein the flame retardant synergist comprises at least one of double hydroxide coated expandable graphite and silicone resin coated expandable graphite;
[0016] Preparation of low-smoke, oil-resistant and flame-retardant polyolefin cable material: high-density polyethylene, POE, hydrogenated nitrile rubber, compatibilizer, flame retardant, flame retardant synergist, coupling agent, lubricant, antioxidant and cross-linking aid are pre-mixed uniformly, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded and granulated, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0017] Optionally, the preparation method of the flame retardant synergist comprises the following steps: after dissolving a metal salt in a container, slowly adding sodium hydroxide, controlling the pH value to be between 9 and 10 to form a layered double hydroxy composite metal hydroxide (LDHs precursor), adding the pretreated expandable graphite to the LDHs precursor, stirring at a constant temperature to allow the LDHs to be evenly coated on the graphite surface, filtering or centrifuging the solid, and drying at an appropriate temperature to obtain double hydroxide-coated expandable graphite (LDH-EG); adding silicone resin to an organic solution to obtain a silicone resin organic solution, then adding expandable graphite, uniformly dispersing it, and then curing it at high temperature, and then crushing and sieving it after cooling to obtain silicone resin-coated graphite (Si-EG) of appropriate particle size, and at least one of the double hydroxide-coated expandable graphite and the silicone resin-coated expandable graphite is a flame retardant synergist.
[0018] Optionally, the metal salt solution is a magnesium nitrate solution or an aluminum nitrate solution.
[0019] Optionally, the organic solvent includes at least one of methanol, toluene, ethanol, acetone and ethyl acetate.
[0020] In order to achieve the above object, the present invention further provides a cable, which is made by any one of the above-mentioned methods for preparing low-smoke, oil-resistant and flame-retardant polyolefin cable materials.
[0021] The beneficial effects of the present invention are as follows: in the present invention, the double hydroxide coated expandable graphite is obtained by coating the layered double metal hydroxide on the expandable graphite, and the LDHs can be decomposed into CO2, H2O, metal oxides, etc. during the combustion process. On the one hand, CO2 and H2O can dilute the combustible gas and O2, and reduce the temperature during combustion; on the other hand, the metal oxide is conducive to the formation of the carbon layer, plays the role of isolating O2 and heat, and further reduces the degradation rate of the substrate; the silicone resin coated expandable graphite and the expandable graphite used have a flame retardant synergistic effect, which promotes the generated carbon layer to have higher strength and better density during the combustion process, and has better flame retardancy and better compatibility with the polymer matrix; the compound use with the flame retardant can reduce its dosage and achieve an excellent flame retardant effect.
[0022] The present invention also uses the flame retardant synergist to prepare low-smoke, oil-resistant and flame-retardant polyolefin cable materials. High-density polyethylene, POE, silica, nitrile rubber, flame retardant synergist, metal hydroxide, cross-linking aid and other additives are used as ingredients of low-smoke, oil-resistant and flame-retardant polyolefin cable material composite materials to form a multifunctional composite material with obvious synergistic effect. Polyolefin provides mechanical strength and processing performance of low-smoke, oil-resistant and flame-retardant polyolefin cable materials. The strong polarity of nitrile rubber and the strong dipole effect of silica interact to form strong adsorption, which improves the mechanical properties and aging resistance of the cable materials, thereby obtaining low-smoke, oil-resistant and flame-retardant polyolefin cable materials with excellent aging resistance, oil resistance and flame retardant properties. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0024] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0025] In order to facilitate the understanding of this embodiment, the symbols, instruments and terms are explained below:
[0026] POE: Polyolyaltha Olfin is an elastic composite material. POE is a copolymer of ethylene and octene, in which the content of the comonomer octene is 20% to 30%.
[0027] PE: Polyethylene is a thermoplastic resin made from the polymerization of ethylene monomers. It is odorless, non-toxic, waxy, and has excellent low-temperature resistance and chemical stability. Because the polymer molecules are connected by carbon-carbon single bonds, it can withstand the corrosion of most acids and alkalis. It is insoluble in general solvents at room temperature, has low water absorption, and has excellent electrical insulation.
[0028] EVA: Ethylene-Vinyl Acetate copolymer, a general-purpose high molecular polymer, is flammable and has a non-irritating burning odor. It has excellent elasticity, flexibility, transparency, insulation, low-temperature flexibility, weather resistance, and chemical corrosion resistance. It is widely used in the manufacture of wire and cable materials, films and other molded products and mixtures, automotive industry parts, adhesives, coatings, etc.
[0029] EMA: Ethylene-Methyl Acrylate copolymer is a polymer material made by copolymerization of ethyl methacrylate and auxiliary monomers. EMA is a transparent, low-density, elastic material with excellent waterproof properties and chemical stability, as well as certain heat resistance and insulation properties.
[0030] With the rapid development of industry and economy, power transmission plays a vital role as the infrastructure of modern society. In many industries, especially in the fields of petrochemical, mining and shipping, the oil resistance and flame retardancy of cables are directly related to the stable operation of equipment and production lines. Traditional polyolefin cables are gradually unable to meet the various performance requirements of modern power transmission. Therefore, the development of a new type of polyolefin cable material with excellent aging resistance, oil resistance and flame retardancy has become the focus of technological innovation.
[0031] In order to solve the above problems, the present invention provides a flame retardant synergist, a low-smoke and oil-resistant flame retardant polyolefin cable material, a preparation method and a cable made from the polyolefin cable material. A flame retardant synergist, the ingredients of the flame retardant synergist include at least one of double hydroxide coated expandable graphite and silicone resin coated expandable graphite.
[0032] In the present invention, the double hydroxide coated expandable graphite is obtained by coating the layered double metal hydroxide on the expandable graphite. During the combustion process, LDHs can be decomposed into CO2, H2O, metal oxides and the like. On the one hand, CO2 and H2O can dilute the combustible gas and O2, thereby reducing the temperature during combustion. On the other hand, the metal oxide is conducive to the formation of a carbon layer, plays a role in isolating O2 and heat, and further reduces the degradation rate of the substrate. The silicone resin coated expandable graphite and the expandable graphite both have a flame retardant synergistic effect, which promotes the generated carbon layer to have higher strength and better density during the combustion process, better flame retardancy and better compatibility with the polymer matrix. The compound use with the flame retardant can reduce its dosage and achieve an excellent flame retardant effect.
[0033] In some embodiments, the flame retardant synergist comprises both double hydroxide-coated expandable graphite and silicone-coated expandable graphite.
[0034] Furthermore, the weight ratio of the double hydroxide coated expandable graphite to the silicone resin coated expandable graphite is (0-15):(0-15).
[0035] In some embodiments, the weight ratio of the double hydroxide coated expandable graphite to the silicone coated expandable graphite is 6:6.
[0036] The present invention also proposes a low-smoke, oil-resistant and flame-retardant polyolefin cable material. The ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material, measured by weight, include: 20-30 parts of high-density polyethylene, 20-35 parts of POE, 15-25 parts of hydrogenated nitrile rubber, 5-10 parts of compatibilizer, 25-45 parts of flame retardant, and 10-15 parts of flame retardant synergist.
[0037] In some embodiments, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material include, by weight: 20-30 parts of high-density polyethylene, 20-35 parts of POE, 15-25 parts of hydrogenated nitrile rubber, 5-10 parts of compatibilizer, 25-45 parts of flame retardant, and 10-15 parts of the above-mentioned flame retardant synergist.
[0038] In some embodiments, the high-density polyethylene has a density of 0.953 g / cm3 and a melt flow rate of 6.7 g / 10 min under a test condition of 190°C / 2.16 kg.
[0039] In some embodiments, the density of POE is 0.905 g / cm3, and the melt flow rate is 0.8 g / 10 min under the test condition of 190°C / 2.16 kg.
[0040] Furthermore, the mass percentage of acrylonitrile in the hydrogenated nitrile rubber is 43%.
[0041] Because the glass transition temperature (Tg) of nitrile rubber with an acrylonitrile content of 40% is -22°C, when the acrylonitrile mass percentage of hydrogenated nitrile rubber is 43%, it means that it can still maintain a certain elasticity at a lower temperature. In addition, with the increase of acrylonitrile content, the tensile strength, heat resistance, oil resistance, air tightness and hardness of hydrogenated nitrile rubber will increase, but the elasticity and cold resistance will decrease. This allows hydrogenated nitrile rubber to maintain physical and mechanical properties equivalent to those at normal temperature under high temperature conditions, and has good heat resistance, aging resistance and oil resistance.
[0042] Furthermore, the compatibilizer includes at least one of POE grafted maleic anhydride, PE grafted maleic anhydride, EVA grafted maleic anhydride and EMA grafted maleic anhydride.
[0043] In some embodiments, the compatibilizer is preferably POE grafted maleic anhydride.
[0044] In some embodiments, the density of POE grafted maleic anhydride is 0.880 g / cm3, and the melt flow rate is 1.0 g / 10 min under the test condition of 190°C / 2.16 kg.
[0045] Furthermore, the flame retardant is a compound of nano silicon dioxide and metal hydroxide, and the weight ratio of the nano silicon dioxide to the metal hydroxide is (10-18): (15-27).
[0046] In some embodiments, the weight ratio of nano-silicon dioxide to the metal hydroxide is 12:24.
[0047] Furthermore, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of a coupling agent, and the coupling agent is a silane coupling agent, which is at least one of vinyl triethoxy silane, vinyl trimethoxy silane, and vinyl tri (β-methoxyethoxy) silane.
[0048] In some embodiments, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material include 1.5 parts of a coupling agent.
[0049] In some embodiments, the coupling agent is preferably vinyltriethoxysilane.
[0050] Furthermore, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of a lubricant, and the lubricant is at least one of stearic acid, calcium stearate, magnesium stearate, polyethylene wax, paraffin and silicone.
[0051] In some embodiments, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material further include 1.5 parts of lubricant.
[0052] In some embodiments, the lubricant is preferably stearic acid.
[0053] Furthermore, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of an antioxidant, and the antioxidant is at least one of dioctylamine, tri[2,4-di-tert-butylphenyl]phosphite, antioxidant PTLTP, antioxidant AO-80, light stabilizer 119, and anti-copper agent MDA.
[0054] In some embodiments, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material further include 1.5 parts of an antioxidant.
[0055] In some embodiments, the antioxidant is preferably bis-octylamine.
[0056] Furthermore, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 2-4 parts of a cross-linking aid, which is at least one of trimethylolpropane triacrylate (TMPTMA), ditrimethylolpropane tetraacrylate (DTMPTA), ethylene glycol diacrylate (EGDA) and ethylene glycol dimethacrylate (EGDMA).
[0057] In some embodiments, the ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material further include 3 parts of a cross-linking aid.
[0058] In some embodiments, the crosslinking aid is preferably TMPTMA.
[0059] In order to solve the above problems, the present invention also proposes a method for preparing a low-smoke, oil-resistant and flame-retardant polyolefin cable material, comprising the following steps:
[0060] S1: preparing a flame retardant synergist: reacting a metal salt solution, sodium hydroxide, expandable graphite and a surfactant through a solution method and then centrifugally drying the resultant to obtain the double hydroxide coated expandable graphite; adding silicone resin to an organic solution to obtain a silicone resin organic solution, then adding expandable graphite, uniformly dispersing the solution and then curing the solution at high temperature, and then cooling the solution and crushing and sieving the solution to obtain silicone coated graphite (Si-EG) of appropriate particle size, wherein at least one of the double hydroxide coated expandable graphite and the silicone coated expandable graphite is a flame retardant synergist.
[0061] Double hydroxide coated expandable graphite is obtained by coating layered double hydroxide on expandable graphite. LDHs can be decomposed into CO2, H2O, metal oxides, etc. during combustion. On the one hand, CO2 and H2O can dilute combustible gas and O2 and reduce the temperature during combustion; on the other hand, metal oxides are conducive to the formation of a carbon layer, which plays a role in isolating O2 and heat, and further reduces the degradation rate of the substrate. The silicone resin and expandable graphite used in the silicone resin coated expandable graphite both have a flame retardant synergistic effect, which promotes the generated carbon layer to have higher strength and better density during the combustion process, better flame retardancy and better compatibility with the polymer matrix, and the use of a flame retardant in combination can reduce its dosage and achieve an excellent flame retardant effect.
[0062] S2: preparing low-smoke, oil-resistant and flame-retardant polyolefin cable material: pre-mixing high-density polyethylene, POE, hydrogenated nitrile rubber, compatibilizer, flame retardant, flame retardant synergist, coupling agent, lubricant, antioxidant and cross-linking aid, and then mixing in an internal mixer to prepare a melt blend;
[0063] In some embodiments, internal mixing is performed in an internal mixer.
[0064] In some embodiments, the internal mixer melt blending temperature is 165° C., and the rotor speed is 40 rpm.
[0065] S3: The molten blend is extruded into granules through an extruder, and then irradiated and cross-linked, and then cooled and dried to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0066] In some embodiments, extrusion granulation is achieved by a twin-screw-single screw extruder.
[0067] In some embodiments, the temperature of zone 1 of the twin-screw extruder is 100°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 160°C, the temperature of zone 4 is 110°C, the temperature of zone 5 is 80°C, the temperature of zone 6 is 80°C, the temperature of zone 7 is 70°C, the temperature of zone 8 is 70°C, and the rotation speed is 150 rpm.
[0068] In some embodiments, the temperature of the single screw extruder zone 1 is 120°C, the temperature of the zone 2 is 125°C, the temperature of the zone 3 is 130°C, the neck temperature is 150°C, the head temperature is 150°C, and the rotation speed is 16 rpm.
[0069] In some embodiments, the low-smoke, oil-resistant and flame-retardant polyolefin cable material is irradiated and cross-linked using a 20 Mrad electron beam.
[0070] Furthermore, the preparation method of the flame retardant synergist comprises the following steps: after dissolving a metal salt in a container, slowly adding sodium hydroxide, controlling the pH value to be between 9 and 10 to form a layered double hydroxy composite metal hydroxide (LDHs precursor), adding the pretreated expandable graphite to the LDHs precursor, stirring at a constant temperature so that the LDHs are evenly coated on the graphite surface, then filtering or centrifuging the solid, and drying at an appropriate temperature to obtain double hydroxide-coated expandable graphite (LDH-EG); adding silicone resin to an organic solution to obtain a silicone resin organic solution, then adding expandable graphite, uniformly dispersing it, and then curing it at high temperature, and then crushing and sieving it after cooling to obtain silicone resin-coated graphite (Si-EG) of appropriate particle size, and at least one of the double hydroxide-coated expandable graphite and the silicone resin-coated expandable graphite is a flame retardant synergist.
[0071] In some embodiments, sodium hydroxide is added to control the pH to preferably 9.5.
[0072] Furthermore, the metal salt solution is one of a magnesium nitrate solution or an aluminum nitrate solution.
[0073] In some embodiments, the metal salt solution is preferably a magnesium nitrate solution.
[0074] Furthermore, the organic solvent includes at least one of methanol, toluene, ethanol, acetone and ethyl acetate.
[0075] In some embodiments, the organic solvent is preferably toluene.
[0076] In order to solve the above problems, the present invention further provides a cable, which is made by any one of the above-mentioned methods for preparing low-smoke, oil-resistant and flame-retardant polyolefin cable materials.
[0077] Embodiment 1:
[0078] Slowly add sodium hydroxide to the metal salt solution, control the pH value to 9 to 10, so as to form an LDHs precursor, add the pretreated expandable graphite to the LDHs precursor, stir at a constant temperature so that the LDHs are evenly coated on the graphite surface, separate the solid by filtering or centrifugation, and dry at an appropriate temperature to obtain double hydroxide-coated expandable graphite; add silicone resin to toluene solvent, slowly add the dried expandable graphite to the silicone resin solution, continue to stir to ensure that the graphite is evenly dispersed, and use a high shear homogenizer to further improve the dispersibility, transfer the mixture to a high-temperature resistant container, put it in an oven for curing, and after curing, take out the product and cool it to room temperature, and crush and sieve it to obtain silicone resin-coated graphite of appropriate particle size, and at least one of the double hydroxide-coated expandable graphite and the silicone resin-coated expandable graphite is a flame retardant synergist.
[0079] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of compatibilizer, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 12 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of lubricant, 1.5 parts of antioxidant and 3 parts of cross-linking aid are pre-mixed uniformly, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0080] Embodiment 2:
[0081] The preparation method is the same as that of Example 1, except that:
[0082] 30 parts of high-density polyethylene, 20 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 12 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0083] Embodiment 3:
[0084] The preparation method is the same as that of Example 1, except that:
[0085] 30 parts of high-density polyethylene, 25 parts of POE, 15 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 12 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0086] Embodiment 4:
[0087] The preparation method is the same as that of Example 1, except that:
[0088] 20 parts of high-density polyethylene, 30 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 12 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0089] Embodiment 5:
[0090] The preparation method is the same as that of Example 1, except that:
[0091] 20 parts of high-density polyethylene, 25 parts of POE, 25 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 12 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0092] Embodiment 6:
[0093] The preparation method is the same as that of Example 1, except that:
[0094] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 18 parts of nano-silicon dioxide, 18 parts of magnesium hydroxide, 12 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0095] Embodiment 7:
[0096] The preparation method is the same as that of Example 1, except that:
[0097] 25 parts of high-density polyethylene, 22 parts of POE, 20 parts of hydrogenated nitrile rubber, 10 parts of POE grafted maleic anhydride, 10 parts of nano-silicon dioxide, 26 parts of magnesium hydroxide, 12 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0098] Embodiment 8:
[0099] The preparation method is the same as that of Example 1, except that:
[0100] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 18 parts of nano-silicon dioxide, 27 parts of magnesium hydroxide, 15 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0101] Embodiment 9:
[0102] The preparation method is the same as that of Example 1, except that:
[0103] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 10 parts of POE grafted maleic anhydride, 18 parts of nano-silicon dioxide, 15 parts of magnesium hydroxide, 12 parts of silicone-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0104] Embodiment 10:
[0105] The preparation method is the same as that of Example 1, except that:
[0106] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 6 parts of double hydroxide-coated expandable graphite, 6 parts of silicone-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0107] Comparative Example 1:
[0108] The preparation method is the same as that of Example 1, except that:
[0109] 35 parts of high-density polyethylene, 35 parts of POE, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 12 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0110] Comparative Example 2:
[0111] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 36 parts of magnesium hydroxide, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0112] Comparative Example 3:
[0113] The preparation method is the same as that of Example 1, except that:
[0114] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 36 parts of magnesium hydroxide, 12 parts of double hydroxide coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0115] Comparative Example 4:
[0116] The preparation method is the same as that of Example 1, except that:
[0117] 25 parts of high-density polyethylene, 25 parts of POE, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 6 parts of double hydroxide-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0118] Comparative Example 5:
[0119] The preparation method is the same as that of Example 1, except that:
[0120] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 20 parts of double hydroxide coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant, and 3 parts of cross-linking aid are mixed evenly, and then mixed in an internal mixer to prepare a melt blend; the melt blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material. Comparative Example 6:
[0121] The preparation method is the same as that of Example 1, except that:
[0122] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 6 parts of silicone-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0123] Comparative Example 7:
[0124] The preparation method is the same as that of Example 1, except that:
[0125] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 20 parts of silicone-coated expandable graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0126] Comparative Example 8:
[0127] The preparation method is the same as that of Example 1, except that:
[0128] 25 parts of high-density polyethylene, 25 parts of POE, 20 parts of hydrogenated nitrile rubber, 7 parts of POE grafted maleic anhydride, 12 parts of nano-silicon dioxide, 24 parts of magnesium hydroxide, 12 parts of expanded graphite, 1.5 parts of coupling agent, 1.5 parts of antioxidant, 1.5 parts of lubricant and 3 parts of cross-linking aid are uniformly mixed, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded through an extruder, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
[0129] The components of Examples 1-10 and Comparative Examples 1-8 and important preparation variables are summarized in Table 1.
[0130] Table 1. Summary of components and important preparation variables for Examples 1-10 and Comparative Examples 1-8 of the present invention
[0131]
[0132] According to the provisions of JB / T10696.6-2007, the low-smoke oil-resistant flame-retardant polyolefin cable materials in the above Examples 1-10 and Comparative Examples 1-8 were tested for tensile strength, elongation at break, change rate of tensile strength at 158°C for 168h, change rate of elongation at break at 158°C for 168h, change rate of tensile strength resistant to No. 20 oil at 100°C for 70h, change rate of elongation at break resistant to No. 20 oil at 100°C for 70h, change rate of tensile strength resistant to No. 0 oil at 70°C for 168h, change rate of elongation at break resistant to No. 0 oil at 70°C for 168h, and vertical burning grade test, and the test results are recorded in the following Table 2:
[0133] Table 2. Performance of Examples 1-10 and Comparative Examples 1-8
[0134]
[0135] According to the above test results, it can be seen that in Examples 1-5, the addition amount of flame retardant and flame retardant synergist does not change. Compared with Example 1, the addition amount of POE in Example 2 is reduced, and the addition amount of high-density polyethylene is increased; in Example 3, the addition amount of hydrogenated nitrile rubber is reduced, and the addition amount of high-density polyethylene is increased; in Example 4, the addition amount of high-density polyethylene is reduced, and the addition amount of POE is increased; in Example 5, the addition amount of high-density polyethylene is reduced, and the addition amount of hydrogenated nitrile rubber is increased; the ratio of the main matrix material in different embodiments is different. By comparing the experimental data of Examples 1-5, it can be concluded that although the prepared cable materials have different data on mechanical properties, aging resistance and oil resistance, they all have excellent mechanical and flame retardant properties, and also show excellent high temperature resistance and oil resistance. Among them, in Example 3, the addition amount of hydrogenated nitrile rubber is reduced, and its oil resistance is relatively poor, which also reflects that the synergistic oil resistance of hydrogenated nitrile rubber and silica in Examples 1-2 and Examples 4-5, the interaction between the two makes the oil resistance of Examples 1-2 and Examples 4-5 relatively better. Compared with Example 1, no hydrogenated nitrile rubber is added to Comparative Example 1, and no nano-silicon dioxide is added to Comparative Example 3. This different formulation leads to a significant decrease in the oil resistance of Comparative Examples 1 and 3, further proving that the strong polarity of nitrile rubber and its strong dipole interaction with silicon dioxide play a vital role in improving the oil resistance of polyolefin cable materials, and the synergistic effect of these two materials significantly improves the oil resistance of the product; Comparative Example 2 does not add expandable graphite coated with double hydroxide. The results show that the vertical combustion grade of Comparative Example 2 drops from V-0 to V-2. This change verifies that when expandable graphite coated with double hydroxide, nano-silicon dioxide and magnesium hydroxide are used in combination, a synergistic flame retardant effect can be produced. This synergistic effect shows that a significant flame retardant effect can be achieved with a smaller amount of additives.Compared with Example 1, low-smoke, oil-resistant and flame-retardant polyolefin cable materials were prepared by changing the amount of flame retardant synergist added in Examples 4-7. It can be concluded from the experimental data that the mechanical properties of Examples 4 and 6 are improved compared with Example 1, but their aging resistance, oil resistance and flame retardant properties are reduced. The mechanical properties of Examples 5 and 7 are reduced compared with Example 1, and their aging resistance and oil resistance are reduced, and the flame retardant properties do not change much. Therefore, when the amount of flame retardant synergist added is too much or too little, the mechanical properties, aging resistance and flame retardant properties cannot be improved. The invention discloses a cable material having good flame retardancy and flame retardancy. Moreover, in comparative example 8, no flame retardant synergist is added, but 12 parts of expanded graphite are added. The experimental results show that the flame retardancy of comparative example 8 is good, but its mechanical properties are poor. Compared with embodiment 1, it can be reflected that the flame retardant synergist proposed in the present invention can not only improve the flame retardancy and help to keep other properties of the material unchanged, but also help to reduce the cost, so that the provided low-smoke and oil-resistant flame retardant polyolefin cable material has excellent high temperature resistance and oil resistance, has extremely high industrial value, and can be widely used and promoted.
[0136] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A flame retardant synergist, characterized in that: The flame retardant synergist comprises at least one of double hydroxide coated expandable graphite and silicone resin coated expandable graphite.
2. The flame retardant synergist according to claim 1, characterized in that The weight ratio of the double hydroxide coated expandable graphite to the silicone resin coated expandable graphite is (0-15): (0-15).
3. A low-smoke, oil-resistant and flame-retardant polyolefin cable material, characterized in that: The ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material are measured in parts by weight and include: High density polyethylene 20-30 parts; POE 20-35 copies; 15-25 parts of hydrogenated nitrile rubber; Compatibilizer 5-10 parts; Flame retardant 25-45 parts; 10-15 parts of the flame retardant synergist according to claim 1 or 2.
4. The low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 3, characterized in that: The mass percentage of acrylonitrile in the hydrogenated nitrile rubber is 43%.
5. The low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 3, characterized in that: The compatibilizer includes at least one of POE grafted maleic anhydride, PE grafted maleic anhydride, EVA grafted maleic anhydride and EMA grafted maleic anhydride.
6. The low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 3, characterized in that: The flame retardant is compounded from nano silicon dioxide and metal hydroxide, and the weight ratio of the nano silicon dioxide to the metal hydroxide is (10-18): (15-27).
7. The low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 3, characterized in that: The ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of a coupling agent, which is a silane coupling agent, which is at least one of vinyl triethoxy silane, vinyl trimethoxy silane and vinyl tri (β-methoxyethoxy) silane.
8. The low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 3, characterized in that: The ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of lubricant, and the lubricant is at least one of stearic acid, calcium stearate, magnesium stearate, polyethylene wax, paraffin and silicone.
9. The low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 3, characterized in that: The ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 1-2 parts of an antioxidant, and the antioxidant is at least one of dioctylamine, tris[2,4-di-tert-butylphenyl]phosphite, antioxidant PTLTP and antioxidant AO-80.
10. The low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 3, characterized in that: The ingredients of the low-smoke, oil-resistant and flame-retardant polyolefin cable material also include 2-4 parts of a cross-linking aid, which is at least one of trimethylolpropane triacrylate (TMPTMA), ditrimethylolpropane tetraacrylate (DTMPTA), ethylene glycol diacrylate (EGDA) and ethylene glycol dimethacrylate (EGDMA).
11. A method for preparing a low-smoke, oil-resistant and flame-retardant polyolefin cable material, characterized in that: The following steps are involved: Preparation of flame retardant synergist: reacting a metal salt solution, sodium hydroxide and expandable graphite by a solution method and then centrifugally drying to obtain the double hydroxide coated expandable graphite; adding expandable graphite to a silicone resin organic solution, and curing the solution solution to obtain the silicone resin coated expandable graphite, wherein the flame retardant synergist according to claim 1 or 2 comprises at least one of double hydroxide coated expandable graphite and silicone resin coated expandable graphite; Preparation of low-smoke, oil-resistant and flame-retardant polyolefin cable material: high-density polyethylene, POE, hydrogenated nitrile rubber, compatibilizer, flame retardant, flame retardant synergist, coupling agent, lubricant, antioxidant and cross-linking aid are pre-mixed uniformly, and then mixed in an internal mixer to prepare a molten blend; the molten blend is extruded and granulated, cooled and dried, and then irradiated and cross-linked to obtain a low-smoke, oil-resistant and flame-retardant polyolefin cable material.
12. The method for preparing the low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 11, characterized in that: The preparation method of the flame retardant synergist comprises the following steps: After dissolving the metal salt in a container, sodium hydroxide is slowly added, and the pH value is controlled to be between 9 and 10 to form a layered double hydroxy composite metal hydroxide (LDHs precursor), the pretreated expandable graphite is added to the LDHs precursor, and the mixture is stirred at a constant temperature so that the LDHs are evenly coated on the graphite surface, and the solid is separated by filtration or centrifugation, and dried at an appropriate temperature to obtain double hydroxide-coated expandable graphite (LDH-EG); Silicone resin is added to an organic solution to obtain a silicone resin organic solution, and then expandable graphite is added, uniformly dispersed and then cured at high temperature, and then crushed and sieved after cooling to obtain silicone resin coated graphite (Si-EG) of appropriate particle size, and at least one of the double hydroxide coated expandable graphite and the silicone coated expandable graphite is a flame retardant synergist.
13. The method for preparing the low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 11, characterized in that: The metal salt solution is one of a magnesium nitrate solution or an aluminum nitrate solution.
14. The method for preparing the low-smoke, oil-resistant and flame-retardant polyolefin cable material according to claim 11, characterized in that: The organic solvent includes at least one of methanol, toluene, ethanol, acetone and ethyl acetate.
15. A cable, characterized in that: The cable is prepared by the preparation method according to claim 11.
Citation Information
Cited By
Halogen-free flame-retardant environment-friendly cable and preparation method thereof
CN121215370A
Halogen-free flame-retardant environment-friendly cable and preparation method thereof
CN121215370B
